2022
DOI: 10.7717/peerj.13135
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatics analysis for the identification of hub genes and signaling pathways related to circANRIL

Abstract: Background Antisense noncoding RNA in the INK4 locus (ANRIL) is located on human chromosome 9p21, and modulation of ANRIL expression mediates susceptibility to some important human disease, including atherosclerosis (AS) and tumors, by affecting the cell cycle circANRIL and linear ANRIL are isoforms of ANRIL. However, it remains unclear whether these isoforms have distinct functions. In our research, we constructed a circANRIL overexpression plasmid, transfected it into HEK-293T cell line, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The expression of certain linear and circular ANRIL transcripts shows tissue-specific patterns; however, the majority of studies have found that linear ANRIL isoforms significantly contribute to atherosclerosis development and CAD [12,13,15,[18][19][20]. In contrast, circular ANRIL isoforms have been shown to confer an atheroprotective role [18,19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of certain linear and circular ANRIL transcripts shows tissue-specific patterns; however, the majority of studies have found that linear ANRIL isoforms significantly contribute to atherosclerosis development and CAD [12,13,15,[18][19][20]. In contrast, circular ANRIL isoforms have been shown to confer an atheroprotective role [18,19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%